CONCEPTUAL FOUNDATIONS OF SOCIAL INDICATORS (Academia Science Repository, 2023)
This article describes the role of social indicators in accurately digitizing the standard of living of the population. The article reflects the history of the emergence of social indicators and the views of world scientists on their formation, as well as their theoretical views. Formulas are presented that show the components of social indicators that are used at the international and national levels to develop indicators that characterize the standard of living of the population in society.